The Prevention of Lifestyle-Related Chronic Diseases an Economic Framework - Sassi, Franco (OECD Health Working Papers, 2008)
This paper provides an economic perspective on the prevention of chronic diseases, focusing in particular on diseases linked to lifestyle choices. The proposed economic framework is centred on the hypothesis that the prevention of chronic diseases may provide the means for increasing social welfare, enhancing health equity, or both, relative to a situation in which chronic diseases are simply treated once they emerge. Testing this hypothesis requires the completion of several conceptual and methodological steps. The pathways through which chronic diseases are generated must be identified as well as the levers that could modify those pathways. Justification for action must be sought by examining whether the determinants of chronic diseases are simply the outcome of efficient market dynamics, or the effect of market and rationality failures preventing individuals from achieving the best possible outcomes. Where failures exist, possible preventive interventions must be conceived, whose expected impact on individual choices should be commensurate to the extent of those failures and to the severity of the outcomes arising from them. A positive impact of such interventions on social welfare and health equity should be assessed empirically through a comprehensive evaluation before interventions are implemented